2012
DOI: 10.1063/1.3696020
|View full text |Cite
|
Sign up to set email alerts
|

A new way to describe the transition characteristics of a rotating-disk boundary-layer flow

Abstract: A new method of graphically representing the transition stages of a rotating-disk flow is presented. The probability density function contour map of the fluctuating azimuthal disturbance velocity is used to show the characteristics of the boundary-layer flow over the rotating disk as a function of Reynolds numbers. Compared with the variation of the disturbance amplitude (rms) or spectral distribution, this map more clearly shows the changing flow characteristics through the laminar, transitional, and turbulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 15 publications
4
53
0
Order By: Relevance
“…However, the amplitude of the wavepacket with the high-amplitude initial disturbance compares better with the result of Lingwood (1996), although it is not certain that the trailing edge of the wavepacket becomes fixed at R CA . However, Imayama et al (2012) suggested that the change in slope at around R = 545 in disturbance growth (their figure 5) could correspond to the so-called 'secondary front' suggested by Viaud, Serre & Chomaz (2011), leading to a cascade of absolutely unstable secondary instabilities and transition to turbulence. This evidence given by Imayama et al (2012) is perhaps the first experimental validation of secondary absolute instability of the primary nonlinear (steep-fronted) global mode shown in the DNS results of Viaud et al (2011).…”
Section: Studymentioning
confidence: 96%
“…However, the amplitude of the wavepacket with the high-amplitude initial disturbance compares better with the result of Lingwood (1996), although it is not certain that the trailing edge of the wavepacket becomes fixed at R CA . However, Imayama et al (2012) suggested that the change in slope at around R = 545 in disturbance growth (their figure 5) could correspond to the so-called 'secondary front' suggested by Viaud, Serre & Chomaz (2011), leading to a cascade of absolutely unstable secondary instabilities and transition to turbulence. This evidence given by Imayama et al (2012) is perhaps the first experimental validation of secondary absolute instability of the primary nonlinear (steep-fronted) global mode shown in the DNS results of Viaud et al (2011).…”
Section: Studymentioning
confidence: 96%
“…To the best of the authors' knowledge no such experiments have yet taken place. Certainly in the Newtonian regime a wealth of literature exists, and this is currently a topic of particular interest, see Imayama et al [22][23][24], for example. Personal communication with these authors has revealed the difficulty of obtaining consistently accurate experimental results; therefore we can only envisage that the introduction of non-Newtonian fluids would serve to significantly complicate any experimental procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[1], see their figure 1. A hot-wire probe, with a single sensor made of platinum, is operated by a constant temperature anemometer (CTA) with an overheat ratio of 0.8.…”
Section: Introductionmentioning
confidence: 96%